Fishing skill in developing country fisheries: The Kedah, Malaysia trawl fishery - Viswanathan, K. Kuperan; Omar, Ishak; Jeon, Yongil; Kirkley, James; Squires, Dale; Susilowati, Indah (Marine Rsources Foundation, 2001)
Fishing skill is perceived to play a crucial role in catching fish. The question arises for fishery managers as to whether or not there are observable and measurable attributes of the skipper or vessel that can be monitored and regulated to account for skipper skill and, hence, this source of fishing capacity. Equating technical efficiency with skipper skill, this paper evaluates technical efficiency and skipper skill in the Kedah, Malaysia, trawl fishery to address this issue. © 2002 Marine Resources Foundation.